The Representation of Ambiguicity in the Song Qolbi Fiil Madinah by Maher Zain Through Roland Barthes's Semiotic Framework - Rika Rahmawati; Rohanda Rohanda; Ahmad Qonit Ad. (Gunung Djati Conference Series, 2025)
The research found that this song contains profound symbols related to spiritual love. The symbol of the heart or qalb is the center of the marker in the semiotics of love in this text. This paper aims to analyze the representation of double meaning in the song Qolbi Fiil Madinah by Maher Zain using Roland Barthes' semiotic approach. The three levels of meaning-denotation, connotation, and myth-illustrate the complexity of understanding a text. This song was chosen because it contains strong religious symbolism and conveys spiritual messages through lyrics that are rich in denotative and connotative meanings. The research method used is descriptive qualitative with Barthes' semiotic analysis technique that includes three stages of meaning: denotation, connotation, and myth. The results show that the song lyrics represent spiritual longing for the Prophet Muhammad SAW and the City of Medina through metaphors, symbols, and poetic diction. The city of Medina is not only interpreted as a geographical place, but also as a symbol of peace of mind and spiritual closeness. Shalawat becomes a semiotic form to convey love for the Prophet Muhammad. The song also functions as a medium of da'wah that conveys religious values and love for the Prophet in an aesthetic and emotional form. This finding shows that religious music can be an effective means of cultural and spiritual communication in modern society. This research is expected to broaden the horizons in the study of literature, music and semiotics, and become a reference in understanding the multiple meanings contained in contemporary Islamic artworks.